2010
DOI: 10.1111/j.1778-428x.2010.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of hyperoxic ventilation during shock

Abstract: SUMMARY Decreased availability of oxygen to metabolizing cells is a major feature of circulatory shock that leads to tissue damage and multiple organ dysfunctions. A wish to alleviate tissue hypoxia underlies the common clinical use of hyperoxic ventilation in shock. Yet, this straightforward approach is met by skepticism that is based on the potential pro‐inflammatory effects of hyperoxia and the acknowledged roles of reactive oxygen species and oxidative stress in tissue injury. A steadily growing body of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…On the other hand, hyperoxia‐induced oxidative stress and oxygen toxicity are major issues of concern in the process of ventilatory oxygen therapy or diving (Thorsen et al, ; Alcaraz‐Garcia et al, ; Bitterman, ; Martin and Grocott, ). Previous studies have demonstrated that an FiO 2 at higher than 90% is lethal and inhibits proliferation and induces apoptosis of both endothelial and epithelial cells via TGFβ‐, NF‐κB‐, or TP53‐dependent signaling pathways (Horowitz, ; O’Reilly, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hyperoxia‐induced oxidative stress and oxygen toxicity are major issues of concern in the process of ventilatory oxygen therapy or diving (Thorsen et al, ; Alcaraz‐Garcia et al, ; Bitterman, ; Martin and Grocott, ). Previous studies have demonstrated that an FiO 2 at higher than 90% is lethal and inhibits proliferation and induces apoptosis of both endothelial and epithelial cells via TGFβ‐, NF‐κB‐, or TP53‐dependent signaling pathways (Horowitz, ; O’Reilly, ).…”
Section: Introductionmentioning
confidence: 99%
“…The current issue of Transfusion Alternatives in Transfusion Medicine highlights the potential as well as the perils of hyperoxic ventilation as a method to stabilize tissue oxygenation with articles dealing with hyperoxia in myocardial infarction, 5 traumatic brain injury 6 and different types of shock 7 . In the first article, Conti comprehensively describes the effects of high inspiratory O 2 concentrations during acute myocardial infarction 5 .…”
mentioning
confidence: 99%
“…The effects of hyperoxic ventilation as treatment of hemorrhagic shock are ambiguous. In his exhaustive review, Bitterman demonstrates that hyperoxia induces an extensive profile of physiological and pharmacological effects that improve tissue oxygenation, exert anti‐inflammatory and antibacterial effects, augment tissue repair mechanisms, and may also decrease oxidative stress during shock 7 . However, in this setting as well, hyperoxic ventilation has the highest efficacy in situations where arteriolar constriction is diminished by anemia‐induced vasodilation or by hypoxia‐sustained perfusion of the vascular bed.…”
mentioning
confidence: 99%
See 1 more Smart Citation